Ivermectin Pharmacokinetics, Metabolism, and Tissue/Egg Residue Profiles in Laying Hens - Moreno Torrejon, Laura (2015)
The goals were to determine the ivermectin (IVM) plasma pharmacokinetics, tissue and egg residue profiles, and in vitro metabolism in laying hens. Experiments conducted were (1) 8 hens were intravenously treated with IVM and blood samples taken; (2) 88 hens were treated with IVM administered daily in water (5 days) (40 were kept and their daily eggs collected; 48 were sacrificed in groups (n = 8) at different times and tissue samples taken and analyzed); (3) IVM biotransformation was studied in liver microsomes. Pharmacokinetic parameters were AUC = 85.1 ng·day/mL, Vdss = 4.43 L/kg, and T1/2el = 1.73 days. Low IVM tissue residues were quantified with the highest measured in liver and skin+fat. IVM residues were not found in egg white, but significant amounts were quantified in yolk. Residues measured in eggs were greater than some MRL values, suggesting that a withdrawal period would be necessary for eggs after IVM use in laying hens.